WISATA PERIKANAN EDUKATIF DENGAN PENDEKATAN ARSITEKTUR EKOLOGIS DI TANJUNG PRIOK - Kusumo Hastuti; Musyawaroh Musyawaroh; Tri Joko Daryanto (ARSITEKTURA, 2015)
The background  that make educational fishery tourism in Tanjung kodok feasible to be developed is the opportunity to improve tourism potency in Tanjung Kodok, Lamongan Regency, to raise effectiveness of fishery which is basic potential in Lamongan, and to provide educational recreation for tourists of all ages in Tanjung Kodok. Its problem solving has been formulated by designing resort in Tanjung Kodok, Lamongan regency, with Ecological Architecture based on plan and design concept.The aim that can be attained of the research  is making a green resort generally for Indonesian people and especially for East Java People in order to enjoy educational fishery tourism in Tanjung Kodok without putting aside its Ecological Architecture approach. Method used to solve the threat of environmental damage is applying Ecological Architecture on its plan and design.The design concept related to Ecological Architecture approach includes building orientation facing the north and south, vertical garden installment as a sunscreen for an open side facing besides north and south,  the application of fountain as natural cooler in the site, the use of trees as natural shade on public area, mangrove plantation for shore conserving, the utilizing of raindrop reservoir located on the site, and the application of plants roof on every building.  Keywords: Educational Fishery Tourism, Ecology Architecture, Plants Roof, Vertical Garden